XXV ALL-RUSSIA YOUTH CONFERENCE ON STRUCTURE OF LITHOSPHERE AND GEODYNAMICS, IRKUTSK, RUSSIA, APRIL 23–28, 2013 - V. A. Babicheva; A. A. Rybchenko; I. A. Filinov (Геодинамика и тектонофизика)
The article presents an overview of the XXV All-Russia Youth Conference on Structure of Lithosphere and Geodynamics. It took place on April 23-28, 2013 at the Institute of the Earth’s Crust in Irkutsk.